2014
DOI: 10.1080/02705060.2014.930359
|View full text |Cite
|
Sign up to set email alerts
|

Responses of gizzard shad and white crappie to introductions of palmetto bass

Abstract: Palmetto bass (female striped bass Morone saxatilis £ male white bass Morone chrysops) were stocked into Long Branch Lake, Missouri, USA in an effort to restructure the gizzard shad Dorosoma cepedianum population via predation. The goal of this restructuring was to provide more suitable-size prey for white crappie Pomoxis annularis, thereby improving growth of this important sport fish. Secondarily, palmetto bass may prey on the abundant white crappie population which may reduce density-dependent effects on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This was not an artifact of older ages in the posttreatment period because mean age did not differ between periods for these two lakes. In a previous study, I (Michaletz 2014) also observed an increase in growth of adult Gizzard Shad after hybrid Striped Bass stockings in a reservoir. Because the growth of Gizzard Shad is frequently density dependent (DiCenzo et al 1996; Michaletz 2017), these changes in growth suggest that densities were declining in some lakes, but because of large annual variation in CPUE the tests were unable to detect differences between the periods.…”
Section: Discussionmentioning
confidence: 74%
“…This was not an artifact of older ages in the posttreatment period because mean age did not differ between periods for these two lakes. In a previous study, I (Michaletz 2014) also observed an increase in growth of adult Gizzard Shad after hybrid Striped Bass stockings in a reservoir. Because the growth of Gizzard Shad is frequently density dependent (DiCenzo et al 1996; Michaletz 2017), these changes in growth suggest that densities were declining in some lakes, but because of large annual variation in CPUE the tests were unable to detect differences between the periods.…”
Section: Discussionmentioning
confidence: 74%